2017
DOI: 10.1002/ejoc.201700113
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Negative Extremophile Lipopolysaccharides: Promising Source of Inspiration for a New Generation of Endotoxin Antagonists

Abstract: Extremophiles are microorganisms exhibiting the fascinating capability to thrive in habitats that are considered clearly inhospitable. Extreme-loving microorganisms have acquired ever-increasing importance in the biomedical and pharmaceutical fields, with many of their bioactive products having long been used as life-saving drugs. In this context, extremophile Gram-negative bacterial lipopolysaccharides (LPSs) and their analogues offer many promising opportunities for a variety of biomedical and therapeutic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 179 publications
1
43
0
Order By: Relevance
“…Indeed, it was previously reported that LPSs from non-pathogenic bacteria can act as TLR4/MD-2 antagonists or partial antagonists towards toxic LPSs [ 12 ]. As a consequence, there is a constant search for LPS antagonist candidates inspired by a natural source: namely LPS analogues able to bind the receptorial complex, thus competing with toxic LPSs, but not capable of triggering an effective immune response [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was previously reported that LPSs from non-pathogenic bacteria can act as TLR4/MD-2 antagonists or partial antagonists towards toxic LPSs [ 12 ]. As a consequence, there is a constant search for LPS antagonist candidates inspired by a natural source: namely LPS analogues able to bind the receptorial complex, thus competing with toxic LPSs, but not capable of triggering an effective immune response [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…HEX 311 lipid A (Scheme ) is mainly composed of tetra‐ and triacylated species, that is, a highly hypoacylated species, which might be poorly recognized by the sponge immune system. Moreover, if hexaacylated forms occur, these present a 3+3 distribution of the acyl chains, which are also typically correlated to a weak immunopotential . Therefore, the expression of lipid A with structural features leading to weak immunoactivity might be a key requirement to establish the successful symbiosis between the microbe and sponge.…”
Section: Resultsmentioning
confidence: 99%
“…In some natural lipid A variants, phosphates in positions C1 and C4′ are covalently functionalized with phosphate, ethanolamine, ethanolamine phosphate, ethanolamine di-phosphate ( C. jejuni ), and sugars as glycosylamine, 4-amino-4-deoxy- l -arabinopyranose and d -arabinofuranose [ 41 ].…”
Section: Structure-activity Relationship In Natural and Synthetic mentioning
confidence: 99%
“…The elucidation of new lipid A chemical structures deriving from bacteria species is a field in continuous evolution, and SAR in new lipid A types will provide important information for designing new synthetic TLR4 modulators [ 41 , 52 ].…”
Section: Structure-activity Relationship In Natural and Synthetic mentioning
confidence: 99%